Management of dentoalveolar trauma in a 3-year-old child with Glanzmann's Thrombasthenia, a rare bleeding disorder: Case report and review - Rakesh N Bahadure; Vijaya Dhote; Kulsum Iqbal Sayed; Sandeep Bailwad; Poornima Kodate (Wolters Kluwer Medknow Publications, 2019)
Glanzmann's thrombasthenia (GT) is a rare inherited bleeding disorder characterized by disturbed ability of the blood platelets to gather around the site of a broken blood vessel and fail to form a plug to stop bleeding due to deficiency of a glycoprotein IIb/IIIa in the process of blood clotting and results in moderate-to-severe bleeding on slightest injury to blood vessels. It is typically diagnosed in infancy or early childhood due to mucocutaneous bleeding tendencies. Treatment goals in GT are aimed at control of bleeding. Dentoalveolar trauma in patient with bleeding disorder poses a challenge in pediatric dentistry. The present article reports the successful management of subluxation dental injury in a 3-year-old child with "Glanzmann's thrombasthenia associated with sickle cell anemia." A narrative review of GT is given highlighting the importance of preventive dentistry and anticipatory guidance to reduce potential complications in such patients.